Proceedings of the 6th Unconventional Resources Technology Conference 2018
DOI: 10.15530/urtec-2018-2881314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydraulic Fracturing Fluid Chemistry on Shale Matrix Permeability

Abstract: The URTeC Technical Program Committee accepted this presentation on the basis of information contained in an abstract submitted by the author(s). The contents of this paper have not been reviewed by URTeC and URTeC does not warrant the accuracy, reliability, or timeliness of any information herein. All information is the responsibility of, and, is subject to corrections by the author(s). Any person or entity that relies on any information obtained from this paper does so at their own risk. The information here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 11 publications
1
47
1
Order By: Relevance
“…One possible explanation, as illustrated in Figure 5, is that the barite precipitation at the shale-fluid interface armored the surface, hindering transport of dissolved oxygen to the shale interior. This explanation is supported by another study done by the authors of this work, where the permeability of Pennsylvania Marcellus was measured before and after reaction in fracture fluid with additional Ba 2+ and SO4 2-(i.e., the same condition as used in this study), and the post-reaction permeability was found lower than pre-reaction permeability due to barite precipitation (Alalli et al 2018). .…”
Section: Pyrite Oxidationmentioning
confidence: 45%
“…One possible explanation, as illustrated in Figure 5, is that the barite precipitation at the shale-fluid interface armored the surface, hindering transport of dissolved oxygen to the shale interior. This explanation is supported by another study done by the authors of this work, where the permeability of Pennsylvania Marcellus was measured before and after reaction in fracture fluid with additional Ba 2+ and SO4 2-(i.e., the same condition as used in this study), and the post-reaction permeability was found lower than pre-reaction permeability due to barite precipitation (Alalli et al 2018). .…”
Section: Pyrite Oxidationmentioning
confidence: 45%
“…They identified two types of swelling due to these interactions; crystalline swelling and osmotic swelling, the later posing significant adverse effects on reservoir quality. Alalli et al [18] also noted that injected fluids caused disequilibrium in formation which leads to dissolution and precipitation of minerals in an attempt to return to equilibrium state. Dissolution and precipitation patterns were thus examined in order to identify their impact on reservoir quality.…”
Section: Enhanced Hydrocarbon Recoverymentioning
confidence: 99%
“…Thus, a rock system that contains a few main fractures may have thousands of microcracks. At small scales, experiments have demonstrated how microcracks can be entirely clogged by precipitates (Alalli et al, 2018), and pore-scale simulations have revealed aperture alterations in single fractures (Li et al, 2008) and submillimeter fracture networks in shales (Soulaine & Tchelepi, 2016). At large scales, even state-of-the-art discrete fracture network models, which can simulate flow and transport in complex 3-D fracture networks (Hyman et al, 2015;Karra et al, 2015), become computationally prohibitive if main fractures are to be explicitly resolved together with all associated microcracks.…”
Section: 1029/2019wr025960mentioning
confidence: 99%
“…One major concern is the precipitation (mainly BaSO 4) in shale formations that may block the pathways for gas and oil recovery (Paukert Vankeuren et al, ; Vidic et al, ). Recent experiments show that the fracking fluid can be imbibed into shales through microcracks and react with minerals, causing precipitation or dissolution (Alalli et al, ; Li et al, ). Precipitation may clog the microcracks, which offer pathways for the gas transport from the porous matrix to the hydraulic fractures, while dissolution may increase the fracture conductivity (Alalli et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%